Entrepreneurial Knowledge and Digital Competencies – Keys for a Success of Students Entrepreneurship - Marin, Alina-Andreea; Chitimiea, Andreea (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
In today’s economy, which is extremely challenging and competitive at the same time, many people want to have their own business and manage their own incomes. Entrepreneurship is a key driver of today’s economy. This observation underscores the need to ensure adequate entrepreneurial education, in line with the demands on the labor market. The purpose and role of this experience are to educate students to understand the entrepreneurial activity, to develop their entrepreneurial skills and competencies and the intention to run a business. The learning environment is crucial for a successful entrepreneur and he can generate change. This article describes experiences from developing and using the entrepreneurial learning environment in high schools with a technological profile. In this study 1200 students from three technological high schools were observed, the behavior and the results obtained after studying the specialized economic modules were analyzed. Our goal was to identify the main challenges of these students. In our study, we used a mixed-method: questionnaires, topic-based interviews, direct and participatory observation as data collection methods. According to our results, the main challenges were: difficulties in understanding new entrepreneurial notions due to traditional teaching methods, lack of ICT skills, lack of team learning principles and inefficient communication within a group.